Cystatin C Is a More Reliable Biomarker for Determining eGFR to Support Drug Development Studies. (18th May 2018) - Kar, Sumit; Paglialunga, Sabina; Islam, Rafiqul
Abstract: Glomerular filtration rate (GFR) is routinely used as a surrogate endpoint for the development of investigational drugs in clinical trials. GFR and staging of chronic kidney disease are typically assessed by measuring the concentration of endogenous serum biomarkers such as albumin and creatinine. However, creatinine is subject to high biological variability, and levels of creatinine do not rise until nearly 50% of kidney function is damaged, leading to inaccurate chronic kidney disease staging and false negatives. A newer biomarker for GFR, cystatin C, has been shown to be subject to less biological interference and more sensitive to early declines in kidney function. Cystatin C has also been shown to outperform creatinine as an indicator of true GFR and to add information about the occurrence of acute kidney injury. Comparison studies of cystatin C and creatinine continue to demonstrate its increased accuracy and sensitivity for changes in true GFR. While challenges remain for use of cystatin C, international agencies and working groups continue to validate cystatin C as a biomarker and accompanying GFR estimating equations for diagnostic and drug development use. In this review, we summarize these comparison studies, regulatory and industry guidelines, and clinical trial case studies for use of cystatin C in drug development.